Editorial for the Special Issue: "Targeting β-Lactamases to Fight Bacterial Resistance to β-Lactam Antibiotics" - Cecilia Pozzi (MDPI AG, 2020)
In bacteria, a major resistance mechanism to β-lactam antibiotics is the production of one or more β-lactamase enzymes [...]